A new felt scale genus (Hemiptera: Sternorrhyncha; Eriococcidae) from Papua New Guinea, with descriptions of two new species - Kozár, Ferenc; Benedicty, Zsuzsanna Konczné; Hodgson, Chris (Zootaxa, 2008)
A new eriococcid genus, Pseudomontanococcus Kozár & Hodgson, is introduced to take two new species, P. martini Kozár & Konczné Benedicty and P. baloghi Kozár & Konczné Benedicty, both from Papua New Guinea. The adult females and 2 nd -instar female nymphs of both species are described, as are the adult male and 2 nd -instar male of P. martini.